INVESTIGATING BANKS’ PERFORMANCE FOR TURKEY: AN APPLICATION OF PROMETHEE METHOD - Semin Paksoy; Mehmet Fatih Tıraş (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Bank failures bring high costs to every part of a country’s economy. If the necessary early warnings regarding the performance of the banks can be taken on time by the officials, policy makers and intuitions concerned, bank failures can be prevented and a more robust financial environment can be sustained. Therefore, the objective of this paper is to measure the performance and failure risk of Turkish deposit banks and to obtain ranking of the banks based on their financial ratios. To this end, we benefit from a data set which allows us to compare the current banks not only on the basis of their present relative position, but also on the basis of their position to the banks failed between 1997 and 2003. Our principal findings show that, some of privately owned and all of publicly owned current banks are quite sound in terms of their financial ratios while some of privately and foreign-owned banks have significantly poorer performance in terms of the ratios considered. Besides, our results unexpectedly show that two of previously failed banks are found to rank in a better position compared to some of currently operating banks in Turkey.